Substantial side of justice personality (Journal of actual problems of jurisprudence, 2018)
The paper deals with the content side of justice personality. Also in the work comprehensively investigated features of formation of legal consciousness.The paper also focuses on the nature and importance of justice. The main conclusions and position of the author may be used in enhancing the legal awareness and legal education of the Kazakhstan society.Key words: state, legal state, legal culture, legal education, the state, the public authority, the activities of the State.